(untitled) (The Peerian Journal, 2024)
The performance process forms a system of signs in its operations that relies on its generation on the laws and relationships that the codes generate in the process of extending the relationships between the signifier and the signified in the formation of the sign based on the code and its generation and composition in a multi-level operation in terms of internal and external relationships, structural and reciprocal, and transformation that are formed by the construction of the code and linking the form to the content and the signifier to the signified, and what is formed from cultural operations at the local or global level in the formation of the performance system on the stage. The researcher worked on building his research into four chapters to define and build the operations and analysis of the encryption process in the construction and formation of the semiotic system and its transformations in the performance of Romeo and Juliet in Baghdad, considering that the sample model acquires multiple and diverse codes between global and local operations and the transformation between them.